Zachowania strategiczne przedsiębiorstw działających w klastrach - Niemczyk, Jerzy (Enterprises' strategic behaviour in clusters, 2007)
The aim of this paper is to show some characteristic behaviours of enterprises which operate in clusters. Theoretical model used for analyzing such behaviours is net strategy model. This model includes, in its background, entire strategic management options and also some relatively new option. The “new” is net strategy, it means identifying and shaping innovative cooperative construction.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (5); 2007; nr 1187, s. 24-32